Passive smoking exposure and the risk of hypertension among non-smoking adults: the 2015-2016 NHANES data - Onoja Matthew Akpa; Akinkunmi Paul Okekunle; Jeffery Osahon Asowata; Babatunde Adedokun (BMC, 2021)
Abstract Background Hypertension is a major public health problem and a prominent risk factor for cardiovascular diseases. However, whether passive smoking exposure (PSE) is associated with the risk of hypertension is scarcely understood. This study assessed the association between PSE and the risk of hypertension among adults (≥18 years) in the United States of America. Methods Three thousand and sixty-seven adults were identified from the 2015-2016 National Health and Nutrition Examination Survey and the association between PSE and hypertension (adjusting for relevant confounders) was examined using multivariable adjusted-logistic regression analysis at P < 0.05. Results Mean age of respondents was 46.5 ± 17.9 years. Overall, 23.7% of respondents reported PSE and 32.6% were hypertensives (of which only 14.3% were aware of their hypertensive state) Also, adjusted odds of hypertension for participants with PSE was 1.038 (1.037, 1.040), P < 0.0001, in the overall population. Also, PSE aggravated odds of hypertension among young adults - < 60 years (aOR: 1.095, 95CI%: 1.094 to 1.097), P < 0.0001, and old adults - ≥60 years (aOR: 1.110, 95% CI: 1.108 to 1.113), P < 0.0001. Similarly, PSE was associated with increased odds of hypertension among women (aOR: 1.240, 95% CI: 1.238 to 1.242), P < 0.0001 but not among men (aOR: 0.755, 95% CI: 0.754 to 0.757), P < 0.0001. Conclusions PSE was independently associated with the risk of hypertension particularly among women, young and old adults. A multi-ethnic longitudinal cohort may help ascertain causality and provide more evidence for appropriate interventions.